In vitro and in silico evaluation of ACE2 and LOX inhibitory activity of origanum essential oils and carvacrol - Demirci, Fatih; Teralı, Kerem; Karadağ, Ayşe Esra; Biltekin, Sevde Nur; Ak Sakallı, Ezgi; Demirci, Betül; Koşar, Müberra; Başer, Kemal Hüsnü Can (Georg Thieme Verlag KG, 2023)
Origanum spp. are used both for culinary purposes and for their biological activities. In this study, commercial Origanum majorana, Origanum minutiflorum, Origanum vulgare, and Origanum onites essential oils and their prominent constituent carvacrol were evaluated for their in vitro and in silico angiotensin-converting enzyme 2 and lipoxygenase enzyme inhibitory potentials. The essential oils were analysed by gas chromatography-flame ionisation detection and gas chromatography-mass spectrometry, where carvacrol was identified as the major component (62?-?81%), confirming the quality. In vitro enzyme inhibition assays were conducted both with the essential oils (20?µg/mL) and with carvacrol (5?µg/mL). The comparative values of angiotensin-converting enzyme 2 percent inhibition for O. majorana, O. minutiflorum, O. vulgare, and O. onites essential oils were determined as 85.5, 79.1, 74.3, and 42.8%, respectively. As a result of the enzyme assays, carvacrol showed 90.7% in vitro angiotensin-converting enzyme 2 inhibitory activity. The in vitro lipoxygenase inhibition of the essential oils (in the same order) was 89.4, 78.9, 81.1, and 73.5%, respectively, where carvacrol showed 74.8% inhibition. In addition, protein-ligand docking and interaction profiling was used to gain structural and mechanistic insights into the angiotensin-converting enzyme 2 and lipoxygenase inhibitory potentials of major Origanum essential oil constituents. The in silico findings agreed with the significant enzyme inhibition activity observed in vitro. Further in vivo studies are suggested to confirm the safety and efficacy of the oils.
Keywords: Lamiaceae; Origanum Spp.; Essential Oil; ACE2; LOX; Carvacrol